Types Of Facial Expressions In The Holy Qur'an - Kahramonovich, Muydinov Pakhlavon (Indonesian Journal Publisher, 2024)
The Holy Qur'an also describes the expressions of the human face and its meaning in different contexts. This allows for a deeper understanding of the spiritual and linguistic aspects of facial expressions. For example, in the Qur'an there are expressions such as the oppressor biting his hand in regret for what he did, or the believers shedding tears after hearing the truth. Such images show the important role of the face in reflecting the human state of mind through non-verbal expressions.